A DECADE TEMPORAL EVOLUTION OF RICE FIELD AREA CHANGES IN KESIMAN VILLAGE, BALI-INDONESIA - Putu Aryastana; Anak Agung Sagung Putri Gita Suari Samitra; Putu Ika Wahyuni; Krisna Himawan Subiyanto; Jason Pajimola Punay (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aim: This research focuses on understanding the extent of rice field loss and the corresponding increase in non-agricultural land to promote sustainable land management and planning. It examines the significant land-use changes in the Jepun Pipil Region, Kesiman Village, Bali, from 2013 to 2024, with a focus on rice fields and non-rice fields. Methodology and results: The study utilizes remote sensing technology and Landsat satellite imagery, applying four vegetation indices (NDVI, EVI, SAVI, and LAI) to analyze temporal changes in land cover. Among these, NDVI proved to be the most effective index for monitoring the transformations. The analysis shows a notable reduction in rice fields, particularly between 2023 and 2024, with a 43.48% decrease due to urban expansion and infrastructure development. Conversely, non-rice fields expanded by 130.43% during the same period, driven by the increasing demand for residential and commercial areas. Conclusion, significance, and impact study: The study highlights the importance of sustainable land-use planning and urges policymakers to strike a balance between development and the conservation of agricultural lands. The findings provide critical insights for local governments and stakeholders in land management and urban planning, contributing to wider efforts in monitoring agricultural land use and shaping effective policy strategies.